THE COTTAGE INDUSTRY OF MUSIC INSTRUMENT MAKING - AESTHETIC AND EXPRESSIONS IN CREATIVE MUSIC WORKS (International Journal of Creative Future and Heritage (TENIAT), 2014)
AbstrakKreativiti dalam proses pembuatan alat muzik merangkumi aspek daya imaginasi dari pemikiran asal,ekspresi seni dan budaya, sensitif kepada nilai estetik dan pemerhatian kontekstual. Kepentingan elemenelemen ini menyumbang kepada struktur pembuatan alat muzik yang dapat diterima berdasarkan nilaikualiti estetik dan kepentingan filosofikal selain dari keperluan nilai komersil. Dalam pasaran komersil,kajian ini telah merumuskan bahawa ketiadaan produk instrument muzik buatan tempatan memerlukantindakan susulan dari institusi dan organisasi yang berkaitan. Tulisan ini juga mengupas aktiviti kreatifpembuatan alat muzik yang dapat dijadikan wahana untuk mempromosi dan mengarusperdanakanindustri muzik dalam penjanaan ekonomi kreatif Negara.AbstractCreativity in music instrument making involves the notion of ‘imagination’ from original thoughts, expression ofthe art and culture, aesthetic sensitivity and contextual awareness. These are vital elements of associationscontributing to the structure of music instrument making which can be perceived not just through its commercialpreferences but also through its aesthetic qualities or philosophical significance. Along the commercial lines,findings have concluded that the absence of ‘local-made’ music instrument products in Malaysian musicoutlets, which consequently highly dependable on imported products, are an insights to be addressed byboth related institutions and relevant authorities. This paper too explore some inspiring creative activities inthe cottage industry of music instrument making that serves to propagate and to promote the music industryas a distinctive opportunity and avenue in generating the nation’s creative economy
Keywords: Cottage Industry, Creativity and Aesthetic, Commercialization